Judges training in Brazil. An institutional educational model under construction after the 1988 Constitution - Borges de Freitas, Graça Maria (2011)
The systems for the selection and formation of judges possess certain particularities related to the legal tradition adopted by each country; however, more than their relation with legal system adopted by each country, these selection and formation criteria refer to the place and role of the Judiciary in the organization of the State and in this regard, something than can, under no circumstances, be left aside is that the valuation of the constitutional role of the judge and the strengthening of the principles of a democratic State must be included in the formation of every judge so that the founding principles of the national legal order can be reasserted by the judge every time he applies the law to a specific case.